2013
DOI: 10.1002/ijc.28163
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin sensitizes human tumor cells to NK cell‐ and T‐cell‐mediated killing by augmented TRAIL receptor signaling

Abstract: Doxorubicin (DOX) is an anthracycline antibiotic that is widely used to treat different types of malignancy. In this study, it was studied whether DOX could be used to render tumor cells susceptible to apoptosis by NK and T cells. Pretreatment with subapoptotic doses of DOX sensitized tumor cell lines of various histotypes to both NK and T cells resulting in a 3.7 to 32.7% increase in lysis (2.5 mean fold increase, p < 0.0001) and a 2.9 to 14.2% increase in lysis (3.0 mean-fold increase, p < 0.05), respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 48 publications
(66 reference statements)
5
42
0
Order By: Relevance
“…Such effect was achieved by increasing the sensitivity of TRAIL by up-regulation of TRAIL death receptors and down-regulation of TRAIL decoy receptors. Although previous studies showed that doxorubicin sensitizes cancer cells by activating TRAIL receptors or caspase cascade [11,30,31], the combination treatment further increased expression of TRAIL receptors compared with doxorubicin alone treatment ( Figure 3D). In addition to the upregulation of TRAIL-related apoptosis pathway, we also observed that the combination therapy also upregulated additional cell death pathway, Fas.…”
Section: Discussionmentioning
confidence: 77%
“…Such effect was achieved by increasing the sensitivity of TRAIL by up-regulation of TRAIL death receptors and down-regulation of TRAIL decoy receptors. Although previous studies showed that doxorubicin sensitizes cancer cells by activating TRAIL receptors or caspase cascade [11,30,31], the combination treatment further increased expression of TRAIL receptors compared with doxorubicin alone treatment ( Figure 3D). In addition to the upregulation of TRAIL-related apoptosis pathway, we also observed that the combination therapy also upregulated additional cell death pathway, Fas.…”
Section: Discussionmentioning
confidence: 77%
“…Further, recent advances in our ability to expand NK cells ex vivo have fueled translational research investigating a variety of novel methods to bolster immunity against cancer through the use of adoptive NK cell infusions. [12][13][14][15][16] Until recently, the therapeutic potential of NK cell-based immunotherapy remained largely unexplored because the small number of NK cells isolated after a typical apheresis procedure and the inability to reliably expand large numbers of NK cells ex vivo precluded investigators from pursuing phase 1 trials evaluating for an NK cell dose-response relationship. At present, it is not at all clear what threshold of NK cell numbers is needed to achieve an antitumor effect after adoptive NK cell transfer.…”
Section: Ex Vivo Nk Cell Activation and Expansionmentioning
confidence: 99%
“…The extrinsic pathway can strengthen apoptosis initiated by the cytotoxic drugs. However, there are reports that other anti-cancer drugs stimulate expression of TRAIL (Barbetti et al, 2013, Wennerberg et al, 2013. Actually, equol is one of the most potent anti-oxidant among isoflavones (Arora et al, 1998).…”
Section: Discussionmentioning
confidence: 99%